Qualitative Factors of the Materiality - Raziūnienė, Daiva; Verbickaitė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2019)
In the audit evidence gathering process, the auditor uses a set of assumptions about audit risk factors and determines the level of material error and misstatement. In practice, questions arise as to how the auditor should avoid making mistakes in shaping its approach to the information that is relevant to users of financial statements. The aim of the study is to reveal the basic regulation of qualitative materiality factors. Tasks of the research are to analyze the regulatory provisions of international auditing standards, to identify issues regarding the assessment of qualitative factors of materiality and its influence on decision making process of the auditors. Methods of literature analysis, systematization, abstracting and grouping analysis are used in the article. The analysis of scientific and professional literature has shown that qualitative parameters of significance are not precisely defined in the regulatory provisions, therefore, the auditors are left with a wide range of qualitative materiality factors. These factors can fundamentally change the auditor's decision-making process choosing relevant audit procedures. The auditor must evaluate the qualitative data and information comprehensively and be able to identify qualitative factors of materiality.JEL klasifikacija: M42
Keywords: financial audit; materiality; audit evidence; qualitative factor